Akulturasi Budaya pada Mahasiswa Diaspora - Garsha Athara Yusiputra; Tia Muthiah Umar (Bandung Conference Series: Public Relations, 2023)
Abstract. Study abroad students have the role of transition and cultural adaptation is very important. Researcher intends to examine more deeply how study abroad students deal with cultural acculturation which includes cultural transitions and adaptations that occur abroad during the process of studying. This research uses qualitative methods with an ethnographic study approach to communication, constructivism paradigm, and data collection. by means of observation, interviews, and documentation. Furthermore, researchers used source triangulation as a technique to test the validity of the data. Then the researcher uses the theory put forward by John W. Berry to strengthen and describe how study abroad students deal with cultural acculturation. The results of this study are: to achieve cultural acculturation, diaspora students must go through the first phase, namely the cultural transition. (1) Cultural transition is a period of transition from an old culture to a new one, a phase influenced by cultural background and habits.1 The next phase is (2) Cultural adaptation, adaptation is a process of adjusting to a new culture. With different cultural backgrounds, each diaspora student has its own effective way of achieving cultural adaptation, the (3) obstacle in these two phases is culture shock. The main obstacle is the ability to speak a foreign language.. (4) Cultural acculturation is a process that occurs when a person meets a foreign culture and gradually the culture is accepted. With study abroad students achieving cultural acculturation, they have two cultures and must have the ability to maintain the culture they have. The conclusion of this study, to achieve cultural acculturation, diaspora students must switch or transition from old habits to new ones. Then adapt to adapt to the new culture. Then facing and resolving existing obstacles so that they are accepted by the new culture. And the latter achieves cultural acculturation by accepting new cultures and being able to maintain the cultural identity that diaspora students have. Abstrak. Mahasiswa diaspora tentu saja memiliki peranan transisi dan adaptasi budaya sangatlah penting. peneliti bermaksud untuk mengkaji lebih dalam akan bagaimana mahasiswa diaspora menghadapi akulturasi budaya yang meliputi transisi dan adaptasi budaya yang terjadi di luar negeri selama proses menempuh pendidikan. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi etnografi komunikasi, paradigma konstruktivisme, serta pengumpulan data dengan cara observasi, wawancara, dan dokumentasi. Selanjutnya peneliti menggunakan triangulasi sumber sebagai teknik uji keabsahan data. Kemudian peneliti menggunakan teori yang dikemukakan oleh John W. Berry untuk memperkuat dan menggambarkan bagaimana mahasiswa diaspora menghadapi akulturasi budaya. Hasil dari penelitian ini yakni: untuk mencapai akulturasi budaya, mahasiswa diaspora harus melewati fase pertama yaitu transisi budaya. (1) Transisi budaya adalah masa peralihan budaya lama ke yang baru, fase dipengaruhi oleh latar belakang dan kebiasaan budaya.. Fase berikutnya adalah (2) Adaptasi budaya, adaptasi merupakan proses penyesuaian dengan budaya yang baru. (3) hambatan dalam kedua fase ini adalah gegar budaya. Hambatan yang paling utama yakni kemampuan untuk berbahasa asing. (4) Akulturasi budaya merupakan proses yang terjadi ketika seseorang bertemu dengan budaya asing dan lambat laun budaya itu diterima. Dengan mahasiswa diaspora mencapai akulturasi budaya, ia memiliki dua kebudayaan dan harus memiliki kemampuan untuk menjaga budaya yang ia punya. Kesimpulan dari penelitian ini, untuk mencapai akulturasi budaya mahasiswa diaspora harus beralih atau bertransisi dari kebiasaan lama ke yang baru. Kemudian melakukan adaptasi untuk menyesuaikan dengan budaya baru. Lalu menghadapi dan meresolusikan hambatan yang ada agar diterima budaya baru. Dan yang terkakhir mencapai akulturasi budaya dengan menerima budaya baru dan dapat menjaga identitas budaya yang mahasiswa diaspora miliki.